2017
DOI: 10.1088/1361-6560/aa83f8
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for virtual lung nodule insertion: volumetric and morphometric comparison of projection-based and image-based methods for quantitative CT

Abstract: Virtual nodule insertion paves the way towards the development of standardized databases of hybrid CT images with known lesions. The purpose of this study was to assess three methods (an established and two newly developed techniques) for inserting virtual lung nodules into CT images. Assessment was done by comparing virtual nodule volume and shape to the CT-derived volume and shape of synthetic nodules. 24 synthetic nodules (three sizes, four morphologies, two repeats) were physically inserted into the lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…Results from this study parallel those obtained in a previous study involving high contrast lung lesions (~1000 HU), where TTF was used to model the transfer properties of a CT imaging system . Using a 3D Hausdorff distance metric, Robins et al.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results from this study parallel those obtained in a previous study involving high contrast lung lesions (~1000 HU), where TTF was used to model the transfer properties of a CT imaging system . Using a 3D Hausdorff distance metric, Robins et al.…”
Section: Discussionsupporting
confidence: 72%
“…Using a 3D Hausdorff distance metric, Robins et al. showed that physical and simulated lesion boundaries differed by less than 5%, across multiple doses and reconstruction settings . They also found that the volumetric difference between physical and simulated lesions was <3% on average 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Digital lesion insertion was conducted via a previously validated 3D image domain insertion technique described as Technique B in an earlier publication (see Fig. ).…”
Section: Acquisition Methodsmentioning
confidence: 99%
“…Also, it can often be challenging to establish ground truth in clinical images. Phantom studies are often used as a substitute, but they bear several general limitations, the foremost being a lack of realistic anatomical complexity . Indeed, even sophisticated anthropomorphic phantoms cannot sufficiently simulate lung and liver parenchyma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation